Comparative vertebrate : anatomy - Hyman, Libbie Henrieta (Chicago : University of Chicago Press, 1992)
The textual material of the present revision is based wholly on the study of original literature and advanced treatises.
I. General considerations of animal form -- II. The phylum chordata -- III. Essential features of lower types -- IV. External anatomy and adaptive radiation in gnathostomes -- V. General features of chordate development -- VI. The comparative anatomy of the skin and exoskeleton -- VII. The endoskeleton : the comparative anatomy of the vertebral column -- VIII. The endoskeleton: the comparative anatomy of the girdles -- IX. The endoskeleton: The comparative anatomy of the skull and the visceral skeleton.
Includes index.
Keywords: ANATOMY, COMPARATIVE